FUNCTIONAL CAPACITIES OF THE CARDIOVASCULAR SYSTEM IN STUDENTS WITH DIFFERENT NEUROTISM'S LEVELS - Valentina Dmitrievna Perhurova; Lyudmila Dmitrievna Tsaturyan; Ekaterina Valerevna Elisseeva (Наука. Инновации. Технологии)
Functional capacities of the cardiovascular system during exercises were studied in students with the different neurotism's levels basing on the adaptation potential's data (AP). It was analyzed that initial AP was more in students with high and low neurotism levels than in students with normal neurotism. After exercise stress (by Harvard Step-test methodic) AP increased mostly in persons with high neurotism in accordance with the degree of regulation systems' tension. It was stated that low neurotism, and more often high neurotism, acted negatively on the adaptation to exercise stress. Adaptive reactions of the cardiovascular system during exercises proceeded with severe stress of adaptation mechanisms, under the risk of decreasing adaptive capacities of the organism.